Transcriptome analysis of HPV-induced warts and healthy skin in humans - AL-Eitan, Laith N. (BMC Med Genomics, 2020)
BACKGROUND: The human papillomaviruses (HPV) are a group of viruses that, depending on the strain, can cause cancer or the formation of benign growths known as warts. Scarce information exists with regard to the genetic nature of non-genital cutaneous warts induced by the human papillomavirus (HPV). METHODS: The main purpose of this study is to investigate the differences between the gene expression profiles of common warts and healthy skin in HPV-positive individuals by RNA sequencing on the Illumina HiSeq 2500. After obtaining shave biopsies of common warts and healthy skin from twelve Arab males, we were able to analyze the transcriptomes of 24 paired cases and controls. RESULTS: Common warts were found to possess a highly significant and unique molecular signature. Many of the most up-regulated (KRT16, EPGN, and ABCG4) and down-regulated genes (C15orf59, CYB561A3, and FCGRT) in warts were the subject of little investigation in the published literature. Moreover, the top 500 differentially expressed genes were found to be associated with immune and autoimmune pathways, such as the neutrophil degranulation, toll-like receptor 7/8 (TLR 7/8) cascade, toll-like receptor 9 (TLR9) cascade, and toll-like receptor 10 (TLR10) pathways, among others. CONCLUSIONS: Our findings are particularly important because they serve as the most comprehensive to date with regard to the modulation of human skin gene expression by HPV infection.